Advances in extraction methods, chemical constituents, pharmacological activities, molecular targets and toxicology of volatile oil from Acorus calamus var. angustatus Besser - Bai, Daoming; Li, Xiaoyu; Wang, Shengguang; Zhang, Tianyi; Wei, Yumin; Wang, Qingquan; Dong, Weichao; Song, Jing; Gao, Peng; Li, Yanan; Wang, Shaoping; Dai, Long (Frontiers in Pharmacology, 2022)
Abstract: Acorus calamus var. angustatus Besser (ATT) is a traditional herb with a long medicinal history. The volatile oil of ATT (VOA) does possess many pharmacological activities. It can restore the vitality of the brain, nervous system and myocardial cells. It is used to treat [-various central system, cardiovascular and cerebrovascular diseases. It also showed antibacterial and antioxidant activity. Many studies have explored the benefits of VOA scientifically. This paper reviews the extraction methods, chemical components, pharmacological activities and toxicology of VOA. The molecular mechanism of VOA was elucidated. This paper will serve as a comprehensive resource for further carrying the VOA on improving its medicinal value and clinical use.